(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The article substantiates the relevance of the problem of formation and development of the pedagogical culture of future police officers. Pedagogical culture as a property of a specialist is one of the factors that determines the effectiveness of a specialist’s professional activity. In this regard, the problem of forming a pedagogical culture among future police officers, which is part of the security and defense sector, is relevant. It is shown that the pedagogical culture of a police officer is a component of his professional culture and has a dialectical relationship with other components of the professional culture of police officers, namely, with legal, psychological, political, ethical, aesthetic, communicative and other cultures that complement each other and ensure effective and high-quality performance of official duties of police officers. The peculiarities of the pedagogical culture of law enforcement officers and their dependence on the peculiarities of the professional activity of police officers are considered. The concept of "pedagogical culture" is defined. It is shown that the professional activity of a police officer during work with citizens involves the implementation of educational and educational functions. That is, a police officer should have a pedagogical culture as a professional quality of personality. The profession of a policeman, like any other profession, has its own specifics, which determines the peculiarities of the pedagogical culture of an employee of the security and defense sector, in particular, a police officer. It is important to pay attention to the formation of such psychological qualities of a police officer as memory, thinking, emotions, feelings, mood, stress, speed of mental, emotional and physical reactions. The specified psychological skills and reactions allow you to think rationally, operate with concepts in a purposeful way, understand, analyze and interpret the norms of laws during the implementation of practical law enforcement activities. The formation of pedagogical culture as a professionally significant quality of the personality of the future employee of the security and defense sector requires the formation of not only certain knowledge, abilities and skills of rational communication and behavior in conflict situations and conflicts, but also certain relationships, attitudes and attitudes as components of the defined personality quality. The results of an experimental study of the formation of pedagogical culture among future police officers in the process of their professional training are presented. It was revealed that there was a statistically probable presence of positive dynamics in most indicators in the experimental groups after studying a special course, writing essays and creative works, participating in training and performing and solving problem situations and quest tasks.